Textbook for Small Multiethnics Islands In Indonesia - Ramli, Murni; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri; Masruroh, Nailil (Proceeding of International Conference on Teacher Training and Education, 2016)
More than five ethnics are living in harmony in five inhabited islands of Karimunjawa, the west southernarchipelago of Java Island. Karimunjawa has uniqueness of its society and natural resources. One of thecrucial problems of education in Karimunjawa is the lack of reading resources or textbooks, which arecontextually promoting the localities. Commonly used textbooks describe facts, culture, or society ofcommon Indonesia, but locality, ethnicity-based indigenous knowledge, nature, environment, fishermen life,Â indigenous technology, and ethnicâs harmonious life had not been mentioned yet in those textbooks. ThisÂ research explored and identified what should students of multicultural society learn about their diversityÂ nature and society. The textbooks are suitable for ES grade 4, 5, and 6. The draft of the textbooks had beenÂ validated as quite good by three experts, and need to be revised on content and to be more inquiry based, andsuitable for ES students.